High strength and toughness maraging stainless steel for ultra-low temperature engineering and its manufacturing method

By optimizing the chemical composition and heat treatment process of Martensite, the problem of unstable impact toughness of existing Martensite at extremely low temperatures is solved, and the effects of high strength, high toughness and good extremely low temperature impact toughness are achieved.

JP7665090B2Active Publication Date: 2025-04-18ANSTEEL BEIJING RES INST CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024502646
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-19
Filing Date
2022-10-26
Publication Date
2025-04-18
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

The existing high-strength and high-toughness Martensites have unstable impact toughness at extremely low temperatures (-196°C), and the heat treatment process is complex and energy consumption is high, making it difficult to ensure the uniformity and performance stability of large forged products.

Method used

By optimizing the chemical composition ratio of Martensite, increasing the appropriate amount of Mo elements, controlling the Ti content to avoid the formation of TiN and TiCN, and using appropriate heat treatment processes to form a fine and stable inverter austenite, thereby improving the toughness of the steel and impact toughness at extremely low temperatures.

Benefits of technology

It achieves the stability and excellent impact toughness of Martensite at extremely low temperatures, reduces the complexity and energy consumption of the heat treatment process, and improves the performance uniformity and stability of large-scale forged products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665090000003
    Figure 0007665090000003
  • Figure 0007665090000004
    Figure 0007665090000004
  • Figure 0007665090000001
    Figure 0007665090000001
Patent Text Reader

Abstract

The present invention relates to a high strength and high toughness maraging stainless steel for ultra-low temperature engineering and a method for producing the same, the main components of which are 11.00%-13.00% Cr, 9.00%-11.00% Ni, 2.00%-4.00% Mo, Ti≦0.05%, and 0.001%-0.080% Al, with the balance being iron, harmful elements, and unavoidable impurities, and the steel has a tensile strength of ≧950 MPa at room temperature, a yield strength of ≧900 MPa, an impact toughness Kv2≧150 J at room temperature, and an impact toughness Kv2≧80 J at -196°C. In the present invention, the compounding ratio of the chemical components of the maraging stainless steel is optimized, an appropriate amount of the alloying element Mo is added to the Cr-Ni stainless steel to perform alloying, the amount of Ti added is controlled so as to avoid the formation of large TiN and TiCN inclusions, and an appropriate heat treatment process is performed, thereby forming fine and stable reverse transformed austenite in the steel, significantly improving the toughness of the steel, especially its ultra-low temperature toughness, and greatly improving the overall performance of the maraging stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of maraging stainless steel, and in particular to a high-strength and high-toughness maraging stainless steel for ultra-low temperature engineering and a method for producing the same. [Background technology]

[0002] Maraging stainless steel is a high-strength stainless steel that combines two strengthening effects, transformation strengthening of low carbon martensite and aging strengthening, and has ultra-high strength, good toughness, thermoplasticity, high-temperature hot forgeability, low hardening index and good weldability, and is widely used in important fields such as aerospace, machinery manufacturing and nuclear power. However, with the further development of the aviation industry, new service conditions require further improvements in materials such as high strength, high toughness, high corrosion resistance, and good workability for complex parts, and in particular, materials are required to have higher impact toughness at ultra-low temperatures (-196℃).

[0003] At present, research on maraging stainless steels at home and abroad is mainly focused on high strength performance. For example, the σ 0.2There are maraging stainless steels with a strength of ≥1400MPa, and a "high strength and high toughness maraging stainless steel" disclosed in a Chinese patent application with application number CN200710099335.3. However, such steels are not required to have impact toughness at ultra-low temperatures (-196°C). S03 high strength stainless steel (00Cr12Ni10MoTi maraging stainless steel) developed overseas is mainly reinforced with Ti, but it has been found through practical application that the impact toughness of this steel type at ultra-low temperatures is unstable. This is because the transformation temperature varies greatly due to minute changes and segregation of Ti. The heat treatment process adopted to ensure low temperature toughness is complicated and has a narrow temperature range, and in large casting and forging products, the production process is complicated, difficult to operate, poor controllability, and high energy consumption, as well as the severe solidification segregation of Ti makes it impossible to ensure the homogenization of large forgings and the uniformity and stability of performance. In addition, because the steel is strengthened by the high Ti content, Ti is likely to combine with N and C to form large inclusions such as TiN and TiCN, which significantly reduces the fatigue performance of large forged products.

[0004] The Chinese patent application with application number 201811597240.9, entitled "Method for improving the low-temperature impact energy of 17-4PH maraging stainless steel forgings by controlling microstructure," discloses that by optimizing the chemical components, the total amount of high-temperature ferrite generated in the steel smelting process is reduced, and by controlling the appropriate forging heating temperature, deformation amount and deformation direction, the high-temperature ferrite in the smelting process is crushed, and the long high-temperature ferrite is forged along a direction perpendicular to its longitudinal direction to upset it, effectively eliminating its directionality, and finally, after two more solution + aging heat treatments, the fine high-temperature ferrite is further removed in the recrystallization process to improve the low-temperature impact energy. Such maraging stainless steel uses high chromium, high copper, and low molybdenum components, with the addition of components such as niobium, titanium, and tantalum, and its component composition and action mechanism are completely different from those of the maraging stainless steel of the present invention. Moreover, its low-temperature impact performance can only achieve KV2 (-40°C) ≧ 27J, and there is no description of the impact toughness of the steel at ultra-low temperatures (-196°C).

[0005] In the "heat treatment method for improving the low-temperature impact toughness of 00Cr12Ni10MoTi maraging stainless steel" disclosed in the Chinese patent application with application number 202010065551.1, the nickel and chromium contents in the maraging stainless steel are close to those of the present invention, but the molybdenum content is much lower than that of the present invention, and the titanium content is much higher than that of the present invention; the heat treatment method includes a double solution heat treatment and an aging heat treatment in this order, and the double solution heat treatment includes three steps, namely, a preliminary solution treatment, a general solution treatment, and a water quenching treatment, and the low-temperature impact toughness reaches AKv (-196 ° C): 90 ~ 140 J. However, the heat treatment process in this technical means is complicated. In contrast, the present invention has the advantages of a wide heat treatment process window, simple operation, high controllability, high efficiency, and low energy consumption. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides a high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering and a manufacturing method thereof. By optimizing the compounding ratio of the chemical components of the maraging stainless steel, alloying it by adding an appropriate amount of alloying element Mo to Cr and Ni stainless steel, controlling the amount of Ti added so as to avoid the formation of large TiN and TiCN inclusions, and performing an appropriate heat treatment process, it is possible to form fine and stable reverse transformed austenite in the steel, significantly improving the toughness of the steel, especially the ultra-low temperature toughness, and greatly improving the overall performance of the maraging stainless steel. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention employs the following means. High strength and high toughness maraging stainless steel for cryogenic engineering has the following components by weight: Cr 11.00%~13.00%, Ni 9.00%~11.00%, Mo 2.00%~4.00%, Ti≦0.05%, Al 0.001%~0.080%; harmful elements in the steel are C≦0.03%, Si≦0.10%, Mn≦0.10%, P≦0.010%, S≦0.008%, [O]≦0.005%, [N]≦0.010%, [H]≦3ppm, Ca≦0.05%, Cu≦0.20%, As≦0.005%, Sn≦0.005%, Sb≦0.005%; the balance is iron and unavoidable impurities.

[0008] The manufacturing method of high strength and high toughness maraging stainless steel for ultra-low temperature engineering includes the following steps: 1) To produce steel ingots or billets; 2) Hot working: the steel ingot or forged billet is homogenized at 1200℃±15℃ for more than 24 hours, and then forged or rolled into a plate or initial billet, with the initial forging temperature or rolling start temperature being 1100-1200℃; 3) Primary solution treatment: Keep at 600-800℃ for 2-14 hours, then cool to room temperature; 4) Aging treatment: Keep at 450~550℃ for 2~20 hours, then air cool to room temperature.

[0009] Furthermore, in the step 1), the steel ingot or the forged billet is obtained by using ultra-low carbon ultra-pure iron or high purity alloy raw material, preparing an electrode rod by vacuum induction, and then performing electric slag remelting + vacuum self-consumption smelting. Furthermore, in step 1), the steel ingot or the cast and forged billet is obtained by using ultra-low carbon ultra-pure iron or high purity alloy raw material, performing AOD or VOD refining, producing an electrode rod by die casting or continuous casting, and then performing electric slag remelting + vacuum self-consumption smelting.

[0010] Furthermore, when the weight of the steel ingot or the billet of the cast and forged product exceeds 20 tons, the ingot or the billet of the cast and forged product is obtained by preparing an electrode rod and then carrying out vacuum self-consumption + electric slag remelting, or by preparing an electrode rod and then carrying out billet preparation by electric slag remelting + vacuum self-consumption + vacuum homogeneous compounding. Furthermore, in step 2), the rolling ratio of the steel ingot is set to 3 or more, and the forging ratio of the forged billet is set to 3 or more. Furthermore, in step 3), the cooling is carried out by using water cooling, oil cooling or air cooling. In addition, the mechanical properties of the manufactured steel plate are Rm≧950MPa, Re≧900MPa, A≧15%, Z≧60%, HV≧300, Kv2≧150J in the longitudinal direction, Kv2≧100J in the transverse direction, and fatigue strength σ -1 ≧500MPa; and the impact toughness at −196° C. is Kv2≧80J in the longitudinal direction and Kv2≧55J in the transverse direction. Effect of the Invention

[0011] The present invention has the following advantageous effects compared to the prior art: 1) The high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use according to the present invention is based on the design concept of toughening by using Mo instead of Ti, and while ensuring high strength, it has better toughness, in particular stable and excellent low-temperature impact toughness and good fatigue performance. 2) The present invention is suitable for producing large castings and forgings, and mainly uses Mo to strengthen the alloy. This ensures the homogenization of large castings and forgings and the uniform stabilization of their performance. It can avoid the difficulty of heat treatment and the instability of low-temperature impact performance due to the significant macrosegregation of Ti in large castings and forgings, while also avoiding the effect of the formation of large TiN and TiCN inclusions on fatigue performance. 3) The present invention has a wide heat treatment process window, simple operation, high controllability, high efficiency and low energy consumption for large castings and forgings. 4) The present invention has a wide range of potential applications in aerospace, marine engineering, energy engineering, etc. [Brief description of the drawings]

[0012] [Figure 1] 1 shows a rotating bending fatigue performance curve of a high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use in Example 1 of the present invention. [Diagram 2] 1 is a rotating bending fatigue performance curve of S03 steel in Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The high strength and high toughness maraging stainless steel for ultra-low temperature engineering according to the present invention has components, by weight percentage, of Cr 11.00%-13.00%, Ni 9.00%-11.00%, Mo 2.00%-4.00%, Ti≦0.05%, and Al 0.001%-0.080%; harmful elements in the steel are C≦0.03%, Si≦0.10%, Mn≦0.10%, P≦0.010%, S≦0.008%, [O]≦0.005%, [N]≦0.010%, [H]≦3ppm, Ca≦0.05%, Cu≦0.20%, As≦0.005%, Sn≦0.005%, and Sb≦0.005%; and the balance being iron and unavoidable impurities.

[0014] The method for producing high strength and high toughness maraging stainless steel for ultra-low temperature engineering according to the present invention includes the following steps: 1) To produce steel ingots or billets; 2) Hot working: the steel ingot or forged billet is homogenized at 1200℃±15℃ for more than 24 hours, and then forged or rolled into a plate or initial billet, with the initial forging temperature or rolling start temperature being 1100-1200℃; 3) Primary solution treatment: Keep at 600-800℃ for 2-14 hours, then cool to room temperature; 4) Aging treatment: Keep at 450~550℃ for 2~20 hours, then air cool to room temperature.

[0015] Furthermore, in the step 1), the steel ingot or the forged billet is obtained by using ultra-low carbon ultra-pure iron or high purity alloy raw material, preparing an electrode rod by vacuum induction, and then performing electric slag remelting + vacuum self-consumption smelting. Furthermore, in step 1), the steel ingot or the cast and forged billet is obtained by using ultra-low carbon ultra-pure iron or high purity alloy raw material, performing AOD or VOD refining, producing an electrode rod by die casting or continuous casting, and then performing electric slag remelting + vacuum self-consumption smelting.

[0016] Furthermore, when the weight of the steel ingot or the billet of the cast and forged product exceeds 20 tons, the ingot or the billet of the cast and forged product is obtained by preparing an electrode rod and then carrying out vacuum self-consumption + electric slag remelting, or by preparing an electrode rod and then carrying out billet preparation by electric slag remelting + vacuum self-consumption + vacuum homogeneous compounding. Furthermore, in step 2), the rolling ratio of the steel ingot is set to 3 or more, and the forging ratio of the forged billet is set to 3 or more. Furthermore, in step 3), the cooling is carried out by using water cooling, oil cooling or air cooling. In addition, the mechanical properties of the manufactured steel plate are Rm≧950MPa, Re≧900MPa, A≧15%, Z≧60%, HV≧300, Kv2≧150J in the longitudinal direction, Kv2≧100J in the transverse direction, and fatigue strength σ -1 ≧500MPa; and the impact toughness at −196° C. is Kv2≧80J in the longitudinal direction and Kv2≧55J in the transverse direction.

[0017] The high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering according to the present invention is designed to be toughened by alloy components, and the microstructure is controlled by using ultra-clean smelting process technology and appropriate heat treatment process technology, thereby ensuring high strength, high toughness, and stable and homogeneous low-temperature performance in large cast and forged products.

[0018] The reasons for designing the high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use (hereinafter, abbreviated as "maraging stainless steel") according to the present invention are as follows. Regarding C, C is not a strengthening element in the maraging stainless steel according to the present invention, but a harmful element. C is likely to form grain boundary precipitates with Cr, which reduces the intergranular corrosion resistance, and can form large inclusions such as TiC and TiCN with elements such as Ti commonly found in maraging stainless steel, impairing the toughness of the steel. Therefore, in the present invention, it is necessary to strictly control the carbon content in the maraging stainless steel, and to control it to 0.03% or less. In addition, the lower the C content, the better, taking into consideration the manufacturing cost overall.

[0019] Regarding Si, in the maraging stainless steel according to the present invention, Si is not a strengthening element or a deoxidizing element, but rather impairs toughness. Therefore, in the present invention, the Si content is controlled to be ≦0.10%. In addition, the lower the Si content, the better, taking into consideration the manufacturing cost as a whole. As for Mn, like Si, an increase in the Mn content in the maraging stainless steel according to the present invention impairs the toughness of the steel. Therefore, in the present invention, the Mn content is controlled to be ≦0.10%. In addition, the lower the Mn content, the better, taking into consideration the manufacturing cost overall.

[0020] Regarding Cr, in the present invention, Cr plays a decisive role in corrosion resistance and also plays a strengthening role. Cr is a strong ferrite forming element and an austenite region reducing element, and can lower the Ms point. When selecting the Cr content range, it is necessary to take into consideration the requirement for corrosion resistance, and it is also necessary to consider the balance with elements such as Ni so that the equivalent content of Ni and Cr falls within the M+A two-phase region range of the Schaeffler equilibrium phase diagram. Therefore, in the present invention, the Cr content is controlled to be between 11.0% and 13.0%.

[0021] Regarding Ni, in the present invention, Ni is crucially important for expanding the austenite stable region, lowering the Ms point, and equilibrating the equivalent content with Cr so as to fall within the M+A two-phase region of the Schaeffler equilibrium phase diagram, as an austenite phase forming element. Ni also has the effects of solid solution strengthening and aging strengthening, and achieves high strength by aging precipitation of nanoscale strengthening phases such as Ni3Mo, Ni3Al, and Ni3Ti with Mo, Al, and Ti. Furthermore, Ni is a major element that maintains the low-temperature toughness of steel. Therefore, in the present invention, the Ni content is controlled to 9.00% to 11.00%.

[0022] As for Mo, the present invention utilizes the toughening effect and corrosion resistance improving effect of Mo. Mo can lower the Ms point and expand the austenite stable region, which is advantageous in obtaining a specified amount of retained austenite in maraging stainless steel and ensuring low-temperature toughness of the steel. Mo can also perform the effect of solid solution strengthening in maraging stainless steel, and acts with Ni to cause aging precipitation of nano-scale Ni3Mo strengthening phases, thereby exerting its remarkable strengthening effect. Furthermore, the alloy element Mo in maraging stainless steel can prevent the precipitation of the precipitated phase along the prior austenite grain boundaries, thereby preventing grain boundary cracking and improving fracture toughness. In the present invention, the Mo content is controlled to the range of 2.0% to 4.0%.

[0023] Regarding Ti, Ti is one of the most effective age-strengthening alloying elements in maraging stainless steels, and can age-precipitate nanoscale Ni3Ti strengthening phases with Ni, greatly improving the strength of the steel. However, Ti has the effect of weakening or impairing the toughness of maraging stainless steels, and the addition of a small amount of Ti significantly increases the strength of the steel, but significantly reduces the toughness. The significant effect of Ti on toughness was verified in the similar maraging stainless steel S03. Since Ti is an element that is prone to segregation in steel, even a small amount of segregation has a significant effect on strength and toughness. For example, in S03 steel, when the Ti content is increased from 0.20% to 0.25%, the low-temperature toughness at -196°C drops sharply from 80J or more to 30J or less, resulting in poor performance. It is difficult to avoid or eliminate macrosegregation in large castings and forgings, and Ti strengthening is very likely to cause poor performance in large forgings, and the corresponding heat treatment process window is very narrow, making engineering applications extremely difficult or impossible. In addition, Ti easily combines with harmful elements C, S, and N in maraging stainless steel to form inclusions such as TiN, TiCN, and TiCS. Because the solidification time of large castings and forgings is long and the precipitation temperature of these inclusions is high, these inclusions can grow sufficiently to reach several tens of microns, and are difficult to fracture and refine in the forging and rolling processes, which greatly impairs the low-temperature impact toughness and fatigue performance of maraging stainless steel. Therefore, in the present invention, the strengthening effect of Ti is abandoned and the toughening effect of Mo is utilized, and the C content in maraging stainless steel is usually controlled to within about 100 ppm, so the problem of intergranular corrosion is almost solved. Therefore, in the present invention, the Ti content can be controlled to 0.05% or less.

[0024] Regarding Al, Al is generally added as a deoxidizer in steel, and in the present invention, the Al content is controlled to 0.080% or less in order to ensure sufficient deoxidation of the steel. The maraging stainless steel according to the present invention is an ultra-low temperature engineering steel, and in order to ensure high low temperature toughness at -196°C, harmful elements in the steel must be strictly controlled. In the present invention, it is necessary to control harmful elements in the steel within the following ranges. The lower the content of harmful elements, the better, taking into consideration the manufacturing cost as a whole. P≦0.010%, S≦0.008%, [O]≦0.005%, [N]≦0.010%, [H]≦3ppm, As, Sn, Sb are each 0.005% or less, Cu≦0.20%, Ca≦0.05%. EXAMPLES

[0025] The following examples are carried out according to the technical means of the present invention, showing detailed embodiments and specific operation procedures, but are not intended to limit the scope of protection of the present invention. The methods used in the following examples are conventional methods unless otherwise specified. [Example 1] In this example, a 50 kg ingot of high strength and high toughness maraging stainless steel was smelted in a vacuum induction furnace. The composition is shown in Table 1. In the alloy composition design, Mo was used as the main strengthening element, and the Mo content was increased to 2.52%; the strengthening effect of Ti was abandoned, and the Ti content was reduced to 0.01% or less; Al was added as a deoxidizer, and its content was controlled to 0.05%. Other harmful elements C, Si, Mn, P, and S were all controlled to low levels. The steel ingot was subjected to high-temperature homogenization diffusion annealing at 1200°C for 24 hours, forged into a square billet with a cross-sectional dimension of 80 mm x 80 mm, and further processed into performance sample billets. After that, it was subjected to solution treatment and aging treatment, and then processed into performance samples and metallographic samples. In this embodiment, the mechanical properties were measured according to GB / T228 "Method of tensile test for metallic materials at room temperature" and GB / T229 "Method of Charpy pendulum impact test for metallic materials". Fatigue properties were measured according to GB T 4337-2015 "Method of rotating bending fatigue test for metallic materials", and the experiment was performed using a PQ1-6 type pure bending fatigue test machine. The results of the measurement of the mechanical properties of the steel in this example are shown in Table 2. After two heat treatments, 750°C x 2h + 500°C x 2h and 850°C x 2h + 700°C x 2h + 750°C x 2h + 500°C x 2h, the tensile strength Rm and yield strength R 0.2 The impact toughness at room temperature exceeded 160 J, and the impact toughness at -196°C exceeded 100 J. -1 The fatigue SN curve is shown in Fig. 1. The high strength and high toughness maraging stainless steel according to the present invention has good strength and low temperature toughness over a wide range of heat treatment processes. The heat treatment process in Example 1 in Table 2 is merely a typical representative example.

[0026] [Example 2] In this example, a 50 kg ingot of high strength and high toughness maraging stainless steel was smelted in a vacuum induction furnace. The composition is shown in Example 2 of Table 1. In the alloy composition design, Mo was used as the main strengthening element, and the Mo content was increased to 3.90%; the strengthening effect of Ti was abandoned, and the Ti content was reduced to 0.04%; Al was added as a deoxidizer, and its content was controlled to 0.07%. Other harmful elements C, Si, Mn, P, and S were all controlled to low levels. The steel ingot was subjected to high-temperature homogenization diffusion annealing at 1200°C for 24 hours, forged into a square billet with a cross-sectional dimension of 80 mm x 80 mm, and further processed into performance sample billets. After that, it was subjected to solution treatment and aging treatment, and then processed into performance samples and metallographic samples. In this embodiment, the mechanical properties were measured according to GB / T228 "Method of tensile test for metallic materials at room temperature" and GB / T229 "Method of Charpy pendulum impact test for metallic materials". Fatigue properties were measured according to GB T 4337-2015 "Method of rotating bending fatigue test for metallic materials", and the experiment was performed using a PQ1-6 type pure bending fatigue test machine. The results of the measurement of the mechanical properties of the steel in this example are shown in Table 2. After two heat treatments, 750°C x 2h + 500°C x 2h and 850°C x 2h + 700°C x 2h + 750°C x 2h + 500°C x 2h, the tensile strength Rm and yield strength R 0.2The impact toughness at room temperature exceeded 150 J and at -196°C exceeded 90 J. -1 exceeded 580MPa. The high strength and high toughness maraging stainless steel according to the present invention has good strength and low temperature toughness over a wide range of heat treatment processes. The heat treatment process in Example 2 in Table 2 is merely a typical representative example.

[0027] [Example 3] In this example, a 50 kg ingot of high strength and high toughness maraging stainless steel was smelted in a vacuum induction furnace. The composition is shown in Table 1. In the alloy composition design, Mo was used as the main strengthening element, and the Mo content was increased to 2.10%; the strengthening effect of Ti was abandoned, and the remaining Ti content was reduced to 0.002%; Al was added as a deoxidizer, and its content was controlled to 0.015%. Other harmful elements C, Si, Mn, P, and S were all controlled to low levels. The steel ingot was subjected to high-temperature homogenization diffusion annealing at 1200°C for 24 hours, forged into a square billet with a cross-sectional dimension of 80 mm x 80 mm, and further processed into performance sample billets. After that, it was subjected to solution treatment and aging treatment, and then processed into performance samples and metallographic samples. In this embodiment, the mechanical properties were measured according to GB / T228 "Method of tensile test for metallic materials at room temperature" and GB / T229 "Method of Charpy pendulum impact test for metallic materials". Fatigue properties were measured according to GB T 4337-2015 "Method of rotating bending fatigue test for metallic materials", and the experiment was performed using a PQ1-6 type pure bending fatigue test machine. The results of the measurement of the mechanical properties of the steel in this example are shown in Table 2. After two heat treatments, 750°C x 2h + 500°C x 2h and 850°C x 2h + 700°C x 2h + 750°C x 2h + 500°C x 2h, the tensile strength Rm and yield strength R 0.2 The impact toughness at room temperature exceeded 175 J and at -196°C exceeded 120 J. -1 exceeded 540MPa. The high strength and high toughness maraging stainless steel according to the present invention has good strength and low temperature toughness over a wide range of heat treatment processes. The heat treatment process in Example 3 in Table 2 is merely a typical representative example.

[0028] [Comparative Example 1] In this comparative example, 50 kg of maraging stainless steel S03 was smelted in a vacuum induction furnace. The components are shown in Table 1. In comparative example 1, the alloy components Cr, Ni, and Mo were all controlled to the upper limit range of S03 steel, and compared to example 1, the Mo content was reduced to 0.71% and the Ti content was increased to 0.16%. That is, Ti was mainly used as a strengthening element, Al was used as a deoxidizer, and its content was controlled to 0.02%, and other harmful elements C, Si, Mn, P, and S were all controlled to low levels. The steel ingot was subjected to high-temperature homogenization diffusion annealing at 1200°C for 24 hours, forged into a square billet with a cross-sectional dimension of 80 mm x 80 mm, and processed into performance sample billets. These were then subjected to solution treatment and aging treatment, and then processed into performance samples and metallographic samples. Table 2 shows the measurement results of the mechanical properties of the S03 steel in this comparative example. In this comparative example, the S03 steel was subjected to two optimized heat treatment processes, 750℃×2h+500℃×2h and 850℃×2h+700℃×2h+750℃×2h+500℃×2h, and then the tensile strength Rm and yield strength R 0.2 Although the impact toughness at room temperature was slightly better than that of Example 1, reaching 170 J or more, the impact toughness at a temperature of -196°C was significantly deteriorated and the material was extremely unstable. The impact energy by the first heat treatment was only 46 J, while the impact energy by the second heat treatment was approximately the same as that of Example 1. This phenomenon does not change even when other heat treatment processes are used. In this comparative example, the fatigue strength at room temperature measured using a sample with the optimum toughness blend was 505 MPa, and the fatigue SN curve is shown in Figure 2. The fatigue strength at room temperature was significantly lower (60 MPa lower) than in Example 1. In addition, the heat treatment process window of this comparative example was significantly narrower than in Example 1, making engineering heat treatment difficult.

[0029] [Comparative Example 2] In this comparative example, 50 kg of maraging stainless steel S03 was smelted in a vacuum induction furnace. The components are shown in Table 1. In comparative example 1, the alloy components Cr, Ni, and Mo were all controlled to the upper limit range of S03 steel, and compared to example 1, the Mo content was reduced to 0.71%, Ti was used as the main strengthening element and its content was increased to the upper limit of the control range of 0.25%, Al was used as a deoxidizer and its content was controlled to 0.06%, and other harmful elements C, Si, Mn, P, and S were all controlled to low levels. The steel ingot was subjected to high-temperature homogenization diffusion annealing at 1200°C for 24 hours, forged into a square billet with a cross-sectional dimension of 80 mm x 80 mm, and processed into performance sample billets. These were then subjected to solution treatment and aging treatment, and then processed into performance samples and metallographic samples. Table 2 shows the measurement results of the mechanical properties of the S03 steel in this comparative example. In this comparative example, the S03 steel was subjected to two optimized heat treatment processes, 750℃×2h+500℃×2h and 850℃×2h+600℃×2h+750℃×2h+500℃×2h, and then the tensile strength Rm and yield strength R 0.2 The fluctuation of impact toughness is large, with the fluctuation range being 900-1100 MPa, the plasticity is low, the impact toughness at room temperature is lower than that of Example 1 and Comparative Example 1, and the impact toughness at a temperature of -196°C is significantly deteriorated, with the maximum value being only 37 J. Even if other heat treatment processes are used, the low temperature toughness cannot be improved.

[0030] [Table 1]

[0031] [Table 2]

[0032] As is apparent from the above examples and comparative examples, the high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering according to the present invention has a good and stable balance of strength and toughness at both room and low temperatures, compared to conventional S03 steel, and its fatigue performance is significantly superior to that of S03 steel. In addition, the heat treatment process window is wide, making it particularly suitable for the production of large castings and forgings required for large equipment, and it has a wide range of possible applications in aerospace, marine engineering, energy engineering, etc. The above are merely preferred embodiments of the present invention, and the scope of protection of the present invention is not limited thereto. Any equivalent replacement or modification made by a person skilled in the art based on the technical means and inventive ideas of the present invention within the technical scope disclosed in the present invention is included in the scope of protection of the present invention.

Claims

1. 1. A high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use, characterized in that its components comprise, in weight percentages, 11.00% to 13.00% Cr, 9.00% to 11.00% Ni, 2.00% to 4.00% Mo, Ti≦0.05%, and 0.001% to 0.080% Al; harmful elements in the steel are C≦0.03%, Si≦0.10%, Mn≦0.10%, P≦0.010%, S≦0.008%, [O]≦0.005%, [N]≦0.010%, [H]≦3 ppm, Ca≦0.05%, Cu≦0.20%, As≦0.005%, Sn≦0.005%, and Sb≦0.005%; and the balance being iron and unavoidable impurities.

2. 2. The method for producing a high strength and high toughness maraging stainless steel for ultra-low temperature engineering use according to claim 1, comprising the steps of: 1) Producing steel ingots or forged billets; 2) Hot working: the steel ingot or forged billet is homogenized at 1200°C ± 15°C for more than 24 hours, and then forged or rolled into a plate or initial billet, with the initial forging temperature or rolling start temperature being 1100-1200°C; 3) Primary solution treatment: Keep at 600-800°C for 2-14 hours, then cool to room temperature; 4) Aging treatment: Keep at 450 to 550°C for 2 to 20 hours, then air cool to room temperature.

3. The method for producing high-strength and high-toughness maraging stainless steel for ultra-low temperature engineering use according to claim 2, characterized in that in step 1), the steel ingot or the cast and forged billet is obtained by using ultra-low carbon ultra-pure iron or high purity alloy raw material to prepare an electrode rod by vacuum induction, and then carrying out electric slag remelting + vacuum self-smelting.

4. The method for producing a high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use according to claim 2, characterized in that in step 1), the steel ingot or the cast and forged billet is obtained by using ultra-low carbon ultra-pure iron or high purity alloy raw material, carrying out AOD or VOD refining, preparing an electrode rod by die casting or continuous casting, and then carrying out electric slag remelting + vacuum self-consumption smelting.

5. 5. The method for producing a high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use according to claim 3 or 4, characterized in that, when the weight of the steel ingot or cast and forged billet exceeds 20 tons, the ingot or cast and forged billet is obtained by producing an electrode rod and then carrying out vacuum self-consumption + electric slag remelting, or by producing an electrode rod and then carrying out billet production by electric slag remelting + vacuum self-consumption + vacuum homogeneous compounding.

6. 3. The method for producing a high-strength, high-toughness maraging stainless steel for ultra-low temperature engineering use according to claim 2, wherein in step 2), the rolling ratio of the steel ingot is set to 3 or more, and the forging ratio of the forged billet is set to 3 or more.

7. The method for producing a high strength and high toughness maraging stainless steel for ultra-low temperature engineering use according to claim 2, characterized in that in step 3), the cooling is performed by water cooling, oil cooling or air cooling.

8. The mechanical properties of the manufactured steel plate are Rm≧950MPa, Re≧900MPa, A≧15%, Z≧60%, HV≧300, Kv2≧150J in the longitudinal direction, Kv2≧100J in the transverse direction, and fatigue strength σ -1 3. The method for producing a high strength and high toughness maraging stainless steel for ultra-low temperature engineering according to claim 2, characterized in that the mechanical strength is Kv2≧500 MPa; and the impact toughness at -196°C is Kv2≧80 J in the longitudinal direction and Kv2≧55 J in the transverse direction.

Citation Information

Patent Citations

  • Deposition hardening type stainless steel

    JP1993125490A

  • Method for producing martensitic stainless steel strip and steel pipe

    JP2002241844A

  • Stainless steel and structure

    JP2004315870A

  • Precipitation hardening martensite based stainless steel and steam turbine member using the same

    JP2012102638A

  • Precipitation-hardening martensitic stainless steel

    JP2020041208A